Avaliação de técnicas de manejo da caatinga através da análise dos atributos físicos e químicos do solo - Gonçalo Filho, Francisco (2015)
The use of forest resources in Northeast Brazil is still made in the irrational and predatory way in most areas of caatinga; because of this biome has suffered constant threats; often this is the simple lack of information on proper techniques of how to manage the forest. It has been observed in practice an increase in society's interest for the development of empirical management plans based mostly on personal needs of demanding inputs coming of forests, according to the law of barriers to predatory exploitation, it is perceived the need for studies that give support to the management of these resources; The objective of this study was to evaluate sustainable management techniques of the caatinga and its effects on recovery of the area and the maintenance of productive capacity, by assessing the physical and chemical soil properties. For that were selected in three areas of Settlement Tabuleiro Grande Design, municipality of Apodi / RN, located in geoenvironment the Apodi Plateau; The first corresponded to 3.2 acres where use was made of thinning techniques, lowering of the enrichment area and control the entry of animals, this being the area of sustainable forest management - AMS; the second with 5.6 hectares was submitted to management that is done in the traditional community, which practices the uncontrolled exploitation of the forest and the overgrazing, which is the area in conventional management - AMC; the third with 2.0 hectares is an integral part of the legal settlement of the reserve, which is the area of native forest - AMN. To preview the effects of management practices on the variation of soil properties after the expiry of five (5) years of intervention in the area of the soil samples were collected at 0-20 and 20-40 cm, and the use of electronic penetrometer for the determination mechanical resistance to penetration - RMP, the same points and the results submitted to analysis of variance and means compared by Tukey test at 1% and 5%. The results indicate management techniques of driving efficiency and AMS, lower values evidenced in bulk density (ds) shown in AMS (0.90 g cm-3) and AMN (1.03 g cm-3) compared AMC ( 1.16 g cm-3), which was directly related to the mechanical resistance to penetration (RMP), considering that higher values observed in the AMC (2337.29 kPa) compared to AMS (1397.30 kPa) and the AMN (1354.53 kPa) in the measured depth (0-40 cm); as the cause of overgrazing in the area, which was confirmed by the values of total porosity that showed higher in AMS, which shows the improvement of soil structure; moisture appeared higher in AMS compared to other areas due to the presence of litter in the area, which favors the maintenance of moisture and contributes to the increase of soil organic matter (SOM) and subsequent retention of more water; in addition to contributing to higher values of match (P), K+ and Mg2 + in AMS, followed by AMN; thereby evident degradation of AMC